A translational preclinical model of interstitial pulmonary fibrosis and pulmonary hypertension: mechanistic pathways driving disease pathophysiology. Issue 9 (11th September 2014) - Jarman, Elizabeth R.; Khambata, Valerie S.; Li, Yun Ye; Cheung, Kenneth; Thomas, Matthew; Duggan, Nicholas; Jarai, Gabor
Abstract Idiopathic pulmonary fibrosis (IPF) is a chronic progressive interstitial lung disease, in which a decline in patient prognosis is frequently associated with the onset of pulmonary hypertension (PH). Animal models exhibiting principle pathophysiological features of IPF and PH could provide greater insight into mechanistic pathways underlying disease progression and a means for evaluating novel therapeutic approaches for intervention. Here, we describe an in vivo disease model, in which animals develop progressive interstitial pulmonary fibrosis and associated PH, as defined by the presence of fibrotic foci adjacent to areas of alveolar injury and remodeling of the pulmonary vasculature. Associated changes in physiological parameters included a decline in lung function and increase in mean pulmonary arterial pressure (mPAP) >25 mmHg. The early fibrotic pathology is associated with a profibrogenic microenvironment, elevated levels of the matrix metalloproteases, MMP‐2, MMP‐7, and MMP‐12, TIMP‐1, the chemoattractant and mitogen, PDGF‐β, and the chemokines CCL2 and CXCL12, that are associated with the recruitment of macrophages, mast cells, and fibrocytes. Principle mechanistic pathways associated with disease pathogenesis are upregulated in the lungs and pulmonary arteries, with sustained increases in gene transcripts for the profibrotic mediator TGF‐β1 and components of the TGF‐β signaling pathway; PAI‐1, Nox‐4, and HIF‐1α. Therapeutic treatment with the ALK‐5/TGF‐β RI inhibitor SB‐525334 reversed established pulmonary fibrosis and associated vascular remodeling, leading to normalization in clinically translatable physiological parameters including lung function and hemodynamic measurements of mPAP. These studies highlight the application of this model in validating potential approaches for targeting common mechanistic pathways driving disease pathogenesis.